How do you solve 9(2x-1)+x=3(6x-3)?

1 Answer
Jan 19, 2016

PEMDAS. x=0

Explanation:

To solve this, you have to simplify the equation using PEMDAS; Parenthesis, Exponent, Multiplication, Division, Addition and Subtraction.

First, simplify what's inside the parenthesis. But this does not apply to given equation. There's also no exponent involved so let's just move to multiplication,

9(2x-1) + x = 3(6x - 3)
(18x - 9) +x = (18x - 9) or (18x - 9 +x = 18x - 9

combine common terms,
19x - 9 = 18x - 9

Then, isolate x by transposing it and combine common terms to solve it,
19x - 18x = -9 +9
x = 0

checking the solution:
x = 0

9(2x-1) + x = 3(6x - 3)
9(2(0)-1) + (0) = 3(6(0) - 3)
9(-1) = 3(-3)
-9 = -9